2015
DOI: 10.2480/agrmet.d-15-00003
|View full text |Cite
|
Sign up to set email alerts
|

Development of an onsite computation scheme of eddy-covariance fluxes

Abstract: Increasingly, agriculture and related industries rely on real-time measurements of surface fluxes and device control based on flux measurements. We have developed a program that computes the eddy-covariance fluxes of CO 2 and H 2 O in real-time on a commercial data logger model. The calculated flux values are targeted for device control. The performance of the program was compared with those of published software programs on maize field data. The calculated fluxes were consistent among the programs. Because pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Instrument heating corrections for an open-path gas analyzer Burba et al, 2008 where shown to have an insignificant effect on the ET and surface energy balance closure, contrary to the findings for the carbon dioxide CO 2 flux Zhu et al, 2012 . Ono andMaruyama 2015 developed an onsite computation scheme for EC fluxes in real-time assessments. Liu et al 2016b introduced flux calculations and QA/QC procedures for an EC system installed on a 325 m meteorology tower in an urban area.…”
Section: Data Processingmentioning
confidence: 99%
“…Instrument heating corrections for an open-path gas analyzer Burba et al, 2008 where shown to have an insignificant effect on the ET and surface energy balance closure, contrary to the findings for the carbon dioxide CO 2 flux Zhu et al, 2012 . Ono andMaruyama 2015 developed an onsite computation scheme for EC fluxes in real-time assessments. Liu et al 2016b introduced flux calculations and QA/QC procedures for an EC system installed on a 325 m meteorology tower in an urban area.…”
Section: Data Processingmentioning
confidence: 99%